2003
DOI: 10.1007/s00253-003-1231-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene biodegradation by an algal-bacterial consortium in two-phase partitioning bioreactors

Abstract: An algal-bacterial consortium formed by Chlorella sorokiniana and a phenanthrene-degrading Pseudomonas migulae strain was able to biodegrade 200-500 mg/l of phenanthrene dissolved in silicone oil or tetradecane under photosynthetic conditions and without any external supply of oxygen. Phenanthrene was only removed when provided in organic solvent, which confirms the potential of two-phase systems for toxicity reduction. Phenanthrene was degraded at highest rates when provided in silicone oil rather than in tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…Cirigliano and Carman (1984) reported that Candida lipolytica, which showed a low level of emulsification activity on glucose, demonstrated inducible emulsification activity on a number of hydrophobic carbon substrates. In the present study, with the exception of strain C. maltosa-like, the emulsification ability levels of the yeast strains in naphthalene were higher than those of C. lipolytica grown on water-immiscible carbon substrates (0.50 to 0.98 EU mL −1 ), and comparable to those of bacterial strains grown in PAHs (1.6 to 1.7 EU mL −1 ; Muñoz et al 2003). We hypothesized that emulsification activities were induced slowly in the five yeast isolates by naphthalene.…”
Section: Discussioncontrasting
confidence: 51%
“…Cirigliano and Carman (1984) reported that Candida lipolytica, which showed a low level of emulsification activity on glucose, demonstrated inducible emulsification activity on a number of hydrophobic carbon substrates. In the present study, with the exception of strain C. maltosa-like, the emulsification ability levels of the yeast strains in naphthalene were higher than those of C. lipolytica grown on water-immiscible carbon substrates (0.50 to 0.98 EU mL −1 ), and comparable to those of bacterial strains grown in PAHs (1.6 to 1.7 EU mL −1 ; Muñoz et al 2003). We hypothesized that emulsification activities were induced slowly in the five yeast isolates by naphthalene.…”
Section: Discussioncontrasting
confidence: 51%
“…The association of PAH-degrading bacteria with eukaryotic phytoplankton may be viewed as a coevolutionary adaptation based on the ability of the phytoplankton to sequester and/or synthesize PAHs. Although photosynthetically enhanced biodegradation of toxic aromatic pollutants has been demonstrated by using artificial combinations of algal-bacterial consortia (60)(61)(62)(63), little is known about this process in natural algal-bacterial assemblages. The association of these organisms may have potentially profound implications for the natural purging of the water column of PAH contaminants and help contribute to the overall health of the marine ecosystem.…”
Section: Resultsmentioning
confidence: 99%
“…Photosynthetically enhanced biodegradation of toxic aromatic pollutants has been demonstrated using artificial algal-bacterial consortia (5,33,42,53). However, there is little known about these processes in natural algal-bacterial assemblages.…”
Section: Discussionmentioning
confidence: 99%